2019
DOI: 10.1098/rsbl.2018.0885
|View full text |Cite
|
Sign up to set email alerts
|

Telomere attrition: metabolic regulation and signalling function?

Abstract: Stress exposure can leave long-term footprints within the organism, like in telomeres (TLs), protective chromosome caps that shorten during cell replication and following exposure to stressors. Short TLs are considered to indicate lower fitness prospects, but why TLs shorten under stressful conditions is not understood. Glucocorticoid hormones (GCs) increase upon stress exposure and are thought to promote TL shortening by increasing oxidative damage. However, evidence that GCs are pro-oxidants and oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(137 citation statements)
references
References 154 publications
(230 reference statements)
5
131
1
Order By: Relevance
“…A recent hypothesis also suggests that telomere shortening may increase during times of substantially increased energy demands due to specific metabolic adjustments (Casagrande and Hau 2019). For instance, a study on humans found that individuals with high physical activity had shorter telomeres than individuals with moderate physical activity (Ludlow et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A recent hypothesis also suggests that telomere shortening may increase during times of substantially increased energy demands due to specific metabolic adjustments (Casagrande and Hau 2019). For instance, a study on humans found that individuals with high physical activity had shorter telomeres than individuals with moderate physical activity (Ludlow et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal exposure to glucocorticoids has been shown to accelerate telomere shortening [25], and therefore variation in prenatal glucocorticoid levels linked to incubation temperature stability could contribute to the observed differences in hatching telomere length, since we found that embryos experiencing unstable incubation conditions had higher plasma glucocorticoid levels and shorter telomeres at hatching. This effect on telomeres could be a consequence of either reduced telomerase activity ( [48], but see [49]) or reprogramming of cellular metabolism as recently proposed by the metabolic telomere attrition hypothesis [32]. However, shorter telomeres at hatching in the high temperature group could not be explained by differences in prenatal glucocorticoid exposure, nor by oxidative stress (see above).…”
Section: Prenatal Growth Rate and Stability As Determinants Of Telomementioning
confidence: 85%
“…Additionally, it is important to identify the underlying mechanisms driving telomere shortening in response to prenatal conditions. While oxidative stress is a first obvious candidate [13], glucocorticoid hormones have been suggested to influence prenatal telomere shortening [25], in a manner that could be independent of oxidative stress but linked to cellular metabolic reprogramming [32].…”
Section: Introductionmentioning
confidence: 99%
“…Telomere shortening during this seasonal transition may be an adaptive response. Indeed, this attrition would contribute to the amplification of the signaling of metabolic debt and therefore to the prioritization of somatic maintenance processes ( Casagrande and Hau, 2019 ). In this respect, telomerase, whose activity varies across species, cell types and life stages ( Gomes et al, 2010 ), represents the most widespread repair mechanism in normal cells.…”
Section: Putative Physiological Costs Of Heterothermymentioning
confidence: 99%